Calcium channels as therapeutic targets in head and neck squamous cell carcinoma: current evidence and clinical trials - Lin, Jinye; Wang, Xijia; Ma, Shibo; Yang, Dunhui; Li, Kang; Li, Dongcai; Zeng, Xianhai (Frontiers in Oncology, 2024)
Head and neck squamous cell carcinoma (HNSCC) originates from the mucosal epithelium of the oral cavity, pharynx, and larynx, and is marked by high rates of recurrence and metastasis. Calcium signaling is associated with the progression of HNSCC and the development of drug resistance. Changes in calcium ion flow can trigger severe pathophysiological processes, including malignant transformation, tumor proliferation, epithelial-mesenchymal transition, and apoptosis evasion. Calcium channels regulate and facilitate these processes. Remodeling of calcium signaling has become one of the most prevalent adaptive mechanisms in cancer cells. Preclinical and clinical evidence indicates that alterations in calcium signaling are crucial for the progression of HNSCC. This review examines the role of calcium channels in HNSCC development and evaluates current clinical trials targeting these channels to assess the feasibility of calcium signaling-based therapies for HNSCC.